Development of Digital Distance Measurement Instrument Based on Arduino Uno for Physics Practicum - Megananda, Amelia; Muzayyanah, Esti; Darmayanti, Hervina Puspita; Priana, Zihan Ika (Impulse: Journal of Research and Innovation in Physics Education, 2021)
Measurement in physics is absolute because it affects the results of theoretical and experimental proofs. Retrieval of distance measurement data for physics experiments also requires high accuracy and a relatively long time because the accuracy in the measurements determines the valid results. Sometimes the available measurement instrument is difficult to access for novice researchers because of the high cost of these measurement instruments. These problems often result in errors and limitations in the implementation of measurements. The relatively long time also slows down data retrieval. This study aims to develop a digital distance measurement instrument based on Arduino Uno for physics practicum. This research is qualitative research using library research methods, field research, designing instruments, and testing hardware and software instruments. Instruments and materials used in this research include the ultrasonic sensor HC-SR04, Arduino Uno r3 kit, LCD, potentiometer, and Arduino IDE software. The result of this research is the digital distance measurement instrument based on Arduino Uno for physics practicum can be a solution for measuring objects with large distances and lengths. This measurement instrument has the smallest value of 1 cm. The design of the Arduino uno-based digital distance measuring device for physics practicum is a practical measurement instrument with the smallest measuring value of 1 cm which can assist students in measuring distances in physics practicum.